معهد الإيمانية الدالويَّة النشأة والأهداف والدور الدعوي: The Islamic Da'wah in Southern Thailand - Referring Maahad Al-Imaniyyah Ad-Dalawiyah As A Model - Hayeemasa , Hasan; Sayed Emam Sallam , Amr Mohammed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص هذه الدراسة تبحث عن الدعوة الإسلامية التي يقوم بها معهد الإيمانية الدالوية بفطاني جنوب تايلاند. ومن أهم الأسباب التي من أجلها تم اختيار هذا العنوان هو البحث عن الدور الذي قام به علماء هذا المعهد ومن ينتمي اليه من الدعاة في الدعوة الإسلامية ،كما أن هذا البحث يكون مرجعا مهما في نشر الدعوة الإسلامية في مجال التربية والمجتمع في جنوب تايلاند. وهذا البحث يهدف إلى عرض كيفية طرق الدعوة الإسلامية التي قام بها الدعاة في نشر العلوم وتعاليم الإسلام في جنوب تايلاند خصوصا في هذا المعهد العريق. وهذا البحث يسير على عدة مناهج وهي المنهج الوصفي والمنهج التحليلي مع الدراسة الميدانية ، وقد تبين من خلال البحث أن العلماء الذين قاموا بالدعوة الإسلامية قد بذلوا جهودهم في إصلاح المجتمع والوطن خصوصا في مجال التعليم ، وهذا المعهد قد نجح في صناعة رجال الدعوة أو الدعاة في جنوب تايلاند والبلاد المجاورة لها. Abstract This study aimed mainly at the Islamic da’wah carried out by the Al-Imaniyyah Ad-Dalawiyyah Faith Institute in Pattani, southern Thailand. One of the most important reasons for which i chose the title for the role played by the scholars of this institute and the preachers belonging to it in the Islamic da’wah. Also, this research is an important reference in spreading the Islamic call in the field of education and society in southern Thailand. This research aims to show how the methods of Islamic da’wah carried out by the preachers in spreading the sciences and teachings of Islam in southern Thailand, especially in this ancient institute. This research is based on several approaches, namely the descriptive approach and the analytical approach, with a field study. It was found through the research that the scholars who carried out the Islamic da’wah have made efforts to reform society and the nation, especially in the field of education. This institute has succeeded in making da’wah men or preachers in southern Thailand and the neighboring countries.